Sketch-Based Spatial Queries for the Retrieval of Human Locomotion Patterns in Smart Environments - de Silva, Gamhewage C.; Yamasaki, Toshihiko; Aizawa, Kiyoharu (Advances in Multimedia, 2009)
A system for retrieving video sequences created by tracking humans in a smart environment, by using spatial queries, is presented. Sketches made with a pointing device on the floor layout of the environment are used to form queries corresponding to locomotion patterns. The sketches are analyzed to identify the type of the query. Directional search algorithms based on the minimum distance between points are applied for finding the best matches to the sketch. The results are ranked according to the similarity and presented to the user. The system was developed in two stages. An initial version of the system was implemented and evaluated by conducting a user study. Modifications were made where appropriate, according to the results and the feedback, to make the system more accurate and usable. We present the details of the initial system, the user study and the results, and the modifications thus made. The overall accuracy of retrieval for the initial system was approximately 93%, when tested on a collection of data from a real-life experiment. This is improved to approximately 97% after the modifications. The user interaction strategy and the search algorithms are usable in any environment for automated retrieval of locomotion patterns. The subjects who evaluated the system found it easy to learn and use. Their comments included several prospective applications for the user interaction strategy, providing valuable insight for future directions.